Frontier Agriculture for Improving Refugee Livelihoods : Unleashing Climate-Smart and Water-Saving Agriculture Technologies in MENA - Verner, Dorte; Vellani, Saleema; Klausen, Anne-Lise; Tebaldi, Edinaldo (World Bank, Washington, DC, 2018)
Many refugee and host populations are food insecure and poor. In Syria, the UNICEF screened 2.3 million children and pregnant and lactating women for acute malnutrition. In Jordan, approximately half of the refugee households have reported reducing the quantity and quality of food and skipping meals. In Lebanon, only 7 percent of refugees are living with acceptable levels of food security. This report shows that frontier agriculture, which comprises climate-smart and water saving agriculture technologies, such as hydroponics, can contribute to improve well-being, including nutritional status for farmers and groups of people that are less integrated into the labor market. In the Middle East and North Africa (MENA), this includes women, youth, and those who are forcibly displaced. Frontier agriculture can leverage scarce resources, such as water and arable land, and promote inclusive economic activities that increase access to nutritious food, improve livelihoods, create jobs, promote entrepreneurship, enhance skills, and build social cohesion. It can also assist with building communities and help recover from the loss of assets and from trauma of fleeing from conflicts. There is an urgency to engage with and support refugee livelihoods. Previous experiences suggest that small-scale hydroponic projects targeting vulnerable populations can be implemented rather quickly and produce meaningful results within a short timeframe.